Свободные и вынужденные колебания толстостенных анизотропных цилиндрических оболочек - Марчук, А.В.; Гнедаш, С.В.; Левковский, С.А. (Прикладная механика, 2017)
У рамках просторової теорії пружності запропоновано два підходи щодо дослідження вільних і вимушених осесиметричних коливань циліндричних оболонок. Вони базуються на поділі даної оболонки на ряд складових оболонок по товщині. У першому підході для апроксимації функцій, що визначаються у плані й по товщині, використано поліноми. У другому – для апроксимації функцій, що визначаються у плані, застосовано лінійні поліноми, а їх розподіл по товщині визначено на основі аналітичного розв'язку відповідної системи диференціальних рівнянь. Необхідність побудови двох підходів обумовлена тим, що їм властиві похибки апроксимації й арифметичних обчислень. При визначенні частот вільних коливань напіваналітичним методом скінченних елементів у комбінації з методом послідовного звуження інтервалу пошуку за початкові зручно приймати значення частот, що отримано на основі скінченно-елементного підходу. Проведено аналіз поведінки оболонок при вільних і вимушених коливаннях у випадку, коли зона навантаження вдвічі менша від товщини оболонки. Two approaches to study of free and forced axisymmetric vibrations of cylindrical shell are proposed within the framework of the spatial theory of elasticity. They are based on representation of the shell in the form of series of shells over the thickness. The first approach uses the linear polynomials in approximation of function that have to be determined in the plane and over the thickness. The second approach also uses the linear polynomials in approximation of function that have to be determined in the plane, but the dependence of functions on thickness is determined from the analytical solution of corresponding system of differential equations. Both approaches have the errors of approximation and arithmetic evaluations. A closeness of results by two approaches can be treated as some element of reliability. While the free vibration frequencies being determined by the semianalytical method of finite elements in combination with the method of successive interval constriction search, it seems to be convenient to choose the initial values of frequencies that are determined by the method of the finite element approach. The behavior of shell for the free and forced vibrations is analyzed in the case when the zone of loading is two times less of the shell thickness.